2017
DOI: 10.1007/s10803-017-3143-z
|View full text |Cite
|
Sign up to set email alerts
|

Peers Influence Prosocial Behavior in Adolescent Males with Autism Spectrum Disorders

Abstract: Peer influence has a profound impact on decision-making in typically developing adolescents. In this study, we examined to what extent adolescent males (age 11-17 years; N = 144) with and without autism (ASD) were influenced by peer feedback on prosocial behavior, and which factors were related to individual differences in peer feedback sensitivity. In a public goods game, participants made decisions about the allocation of tokens between themselves and their group-in absence or presence of peer feedback. Adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…In addition, an important question would be whether peer context can also positively influence behavior of adolescents with MBID. The potential positive effect of prosocial peer-influence has already been demonstrated in experimental study in typically developing adolescents and adolescents with autism (Van Hoorn et al 2016b , 2017 ).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, an important question would be whether peer context can also positively influence behavior of adolescents with MBID. The potential positive effect of prosocial peer-influence has already been demonstrated in experimental study in typically developing adolescents and adolescents with autism (Van Hoorn et al 2016b , 2017 ).…”
Section: Discussionmentioning
confidence: 79%
“…The literature has called for more research with autistic girls (Van Hoorn et al, 2017) as autistic girls (and women) are under-represented in the literature. Van Hoorn et al (2017) purposefully excluded girls from their sample, but one of the goals of this research was to include as high a proportion of autistic girls as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this is an individual difference that operates only in the presence of perceived peer influence, we do not hypothesise that autistic adolescents will show reduced resistance to peer influence. Previous studies have shown distinct patterns of findings when they have looked at autistic and typically developing participants compared to when they have looked at associations with continuous autistic traits (e.g., Yafai et al, 2014;Van Hoorn et al, 2017). Accordingly, as well as looking at the diagnostic group we will also include autistic traits in our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A similar association of autistic traits and lower sensitivity to peer influence was also reported in a study assessing adolescents within the domain of prosocial behaviour. However, this effect was only observed for ‘antisocial’ peer influence (when peers did not cooperate), and did not hold up for ‘prosocial’ peer influence (when peers did cooperate) (Van Hoorn et al 2017). At the group level, this study found autistic adolescents exhibited equivalent social conformity to neurotypical controls (Van Hoorn et al 2017).…”
mentioning
confidence: 99%
“…However, this effect was only observed for ‘antisocial’ peer influence (when peers did not cooperate), and did not hold up for ‘prosocial’ peer influence (when peers did cooperate) (Van Hoorn et al 2017). At the group level, this study found autistic adolescents exhibited equivalent social conformity to neurotypical controls (Van Hoorn et al 2017). Given the very limited literature on the topic and the diversity of the populations studied (e.g., in terms of age) it is unclear whether autism is indeed associated with changes to social conformity.…”
mentioning
confidence: 99%